Political Socialization of the Jakarta General Election Commission Through the KPU Goes to Car Free Day in Increasing Public Political Participation in the 2024 Presidential Election - Hirzia, Atrasina; Rahmawati, Restu (Department of Government Studies, Universitas Syiah Kuala, 2025)
This study aims to analyze the political socialization strategy implemented by The Jakarta General Election Commission (KPU) through the innovative program KPU Goes to Car Free Day in increasing public political participation in the 2024 presidential election. The background of the research is based on the urgency of increasing public awareness and involvement in elections, especially in socio-politically complex urban areas such as Jakarta. This study uses a qualitative approach with descriptive methods and data collection techniques through semi-structured interviews with three main informants, namely members of the DKI Jakarta KPU, researchers from Perludem, and community representatives. The results showed that this program is effective in shaping the political attitudes and behavior of citizens, transferring democratic values, and introducing political guidelines and principles in a communicative and participatory manner. However, the evaluation results also revealed the need for continuity and deepening of the substance of political education so that the values instilled are not superficial or temporary. This Program is considered successful in increasing community participation quantitatively, but its long-term effectiveness requires the support of a more reflective, inclusive, and sustainable political socialization strategy. This research provides an important contribution in strengthening the practice of electoral democracy through an interactive public space-based political socialization approach.